Pengaruh Algoritma Tiktok Terhadap Regulasi Emosi Dan Kesehatan Mental Gen Z Dalam Fenomena Quotes Sedih - Rahmania, Shecha; Abdullah, Mirna Nur Alia; Mujayapura, Muhammad Retsa Rizaldi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to explore the influence of TikTok's algorithm in presenting sad quotes on emotional regulation and mental health among Gen Z. Using a mix method approach, this research combines literature review with exploratory data obtained through a questionnaire. The findings show that TikTok's algorithm plays a significant role in presenting emotional content, which directly affects users' moods and emotional regulation patterns. Most respondents are frequently exposed to sad quote content, which may worsen their emotional condition. Through the perspective of media exposure theory and symbolic interactionism, this study reveals that repeated exposure to emotional content can create emotional attachment and shape social meanings about sadness among Gen Z. Therefore, there is a need for efforts to manage the types of content displayed on TikTok to minimize the negative impact on users' mental health.